True change or return to the past? The evolution of psychiatric care in Italy - Lorettu, Liliana (Medicina Historica, 2019)
The psychiatric care in Italy has undergone radical changes over time, passing from a custodialist form, that of the 1904 law, to a community psychiatric care suggested by the law 180. However, in recent years there has been a further change in which old formulas of custodialism and control of the mentally ill are re-proposed.